Persis: Pergerakan Dakwah di Kota Medan Tahun 2010-2015 - Suryadi Nasution (UIN Sumatera Utara Medan, 2020)
This research aims to identify the Islamic unity movement in the North Sumatera in the field education, preaching, culture, and society environment. The research approach of this study uses case study to describe the development of Islamic Unity in the north sumatera. Techniques for collecting data uses observation, interview, and documentation by gathering the observation result, reduction, data description and result discussion. Commonly the Islamic Unity Movement is divided into two part, first, preaching (Da’wah) movement through the distribution of Islamic Unity’s bulletins in once a fortnight. Second, the establishment of zakat center community that serving distribution of zakat community and giving scholarship in 15% from zakat, infaq and shadaqah’s income.